2022
DOI: 10.1021/acs.energyfuels.2c02692
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Miscibility and Co-feeding Potential of Hydrothermal Liquefaction Biocrude in Refinery Streams: Role of Hydrodeoxygenation

Abstract: Co-processing of hydrothermal liquefaction biocrudes in existing refineries is attracting tremendous attention for large-scale commercialization of sustainable biofuels. As a result of the higher oxygen content, these biocrudes are not compatible with refinery streams; therefore, co-processing requires an essential (stand-alone) prior mild hydrotreating step. Therefore, Spirulina biocrude and mild hydrotreated samples (200, 250, 300, and 340 °C) were comprehensively investigated for their compatibility and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In the co-processing test, little or no catalyst deactivation was observed with ≤10% RCFP blend based on the density of the hydrotreated products. Sharma et al 15 studied miscibility of HTL biocrudes in refinery streams co-processing and concluded the usefulness of theoretical predictions made by Hansen solubility parameters. Zhu et al 16 investigated the deactivation modes of a hydrotreating catalyst used for co-processing HTL biocrude (from wastewater sludge) with straight-run diesel.…”
Section: ■ Co-refining Of Bioliquids and Fossil Oils In Refinery Proc...mentioning
confidence: 99%
“…In the co-processing test, little or no catalyst deactivation was observed with ≤10% RCFP blend based on the density of the hydrotreated products. Sharma et al 15 studied miscibility of HTL biocrudes in refinery streams co-processing and concluded the usefulness of theoretical predictions made by Hansen solubility parameters. Zhu et al 16 investigated the deactivation modes of a hydrotreating catalyst used for co-processing HTL biocrude (from wastewater sludge) with straight-run diesel.…”
Section: ■ Co-refining Of Bioliquids and Fossil Oils In Refinery Proc...mentioning
confidence: 99%